Comparison Physicochemical Characterization of Essential Oils from Gajah and Emprit Ginger Varieties (JURNAL RISET RUMPUN MATEMATIKA DAN ILMU PENGETAHUAN ALAM, 2026)
Ginger (Zingiber officinale) is a high-economic-value essential oil commodity. This descriptive-exploratory study aimed to analyze and compare the physico-chemical profiles of essential oils from emprit ginger (Zingiber officinale var. Amarum) and giant ginger (Zingiber officinale var. Officinale) originating from Dadaprejo Village, Batu City. Essential oil extraction was performed using water distillation, while characterization employed organoleptic testing by 15 panelists, 96% alcohol solubility testing, yield calculation, and Gas Chromatography-Mass Spectrometry (GC-MS) analysis. Physical results showed emprit ginger oil was dominated by deep yellow color (41.7%) with a very strong aroma (41.7%), whereas giant ginger oil was light yellow (35.7%) with a moderate-strong aroma (35.7%). Emprit ginger yield (0.1067%) was higher than that of giant ginger (0.0800%). Both varieties dissolved completely in 96% alcohol at ratios of 1:3 for emprit ginger and 1:4 for giant ginger. Chemical characterization identified 119 volatile compounds in emprit ginger, dominated by cyclic ketone (Ketone, 1-cyclohexen-1-yl methyl, semicarbazone) at 16.15%, while giant ginger exhibited a simpler profile with 35 components, dominated by phenolic aldehyde (4-Hydroxy-2-nitro-m-anisaldehyde) at 7.67%. Thermal degradation during extraction converted sesquiterpene hydrocarbons such as zingiberene into more stable oxygenated groups. In conclusion, var. amarum holds high potential for the pharmaceutical industry due to its high ketone content, while var. officinale is ideal for the food and beverage industry.